What do codes of ethics tell us about impartiality, and what is preferred at the hospital? - Duman, Duygu (Curum) (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The impartiality of the interpreter has long been an important aspect of and an indispensable quality in healthcare interpreting. Official documents on professional ethics created by professional associations around the world refer to impartiality among the fundamental ethical principles to be adhered to. However, the conditions in the workplace and the background of the interpreter might pose significant risks to ensuring the implementation and adoption of ethics in the field. Furthermore, specific conditions of immigration and the quality (or the existence) of interpreter training in the required language combinations may play a role in either facilitating or impeding the implementation of ethical principles. As a country that has been receiving migrants for a relatively short time, Turkey lacks a code of ethics specifically drawn up for healthcare (or community) interpreters and this may well lead to problems in the field. Therefore, the primary objective of this study is to compare healthcare interpreters’ understanding of, preference for and exercise of impartiality with the prescripts of the codes applicable in other countries and to demonstrate how the principle of impartiality unfolds in healthcare contexts. The results of the study demonstrate that helping the patient was the main motivation of the interpreters in the field rather than being guided purely by impartiality. They reported being deliberately on the patient’s side to support them and to ensure that they obtained the required treatment, an approach which contradicts the codes of the associations in the countries that prefer “interpreting” rather than “mediation”. The analysis pointed to the fact that the meaning of impartiality is shaped by the system in which it is laid down. These results suggest that the codes and the attitudes of healthcare interpreters do not coincide as regards impartiality in a country where healthcare interpreting research and practice are emerging and training opportunities are scarce. They can serve as a useful reference point for policymaking and the professionalization of healthcare interpreters.